Combining Ascochyta blight and Botrytis grey mould resistance in chickpea through interspecific hybridization - KAUR, Livinder; SIRARI, Asmita; KUMAR, Dinesh; SINGH SANDHU, Jit; SINGH, Sarvjeet; KAPOOR, Karan; SINGH, inderjit; GOWDA, C.L. Laxmipati; PANDE, Suresh; GAUR, Pooran; et al. (Phytopathologia Mediterranea, 2012)
Ascochyta blight (AB) caused by Ascochyta rabiei (Pass.) Labr. and Botrytis grey mould (BGM) caused by Botrytis cinerea (Pers. ex Fr.) are important diseases of the aerial plant parts of chickpea in most chickpea growing areas of the world. Although conventional approaches have contributed to reducing disease, the use of new technologies is expected to further reduce losses through these biotic stresses. Reliable screening techniques were developed: ‘field screening technique’ for adult plant screening, ‘cloth chamber technique’ and ‘growth chamber technique’ for the study of races of the pathogen and for segregating generations. Furthermore, the ‘cut twig technique’ for interspecific population for AB and BGM resistance was developed. For introgression of high levels of AB and BGM resistance in cultivated chickpea from wild relatives, accessions of seven annual wild Cicer spp. were evaluated and identified: C. judaicum accessions 185, ILWC 95 and ILWC 61, C. pinnatifidum accessions 188, 199 and ILWC 212 as potential donors. C. pinnatifidum accession188 was crossed with ICCV 96030 and 62 F9 lines resistant to AB and BGM were derived. Of the derived lines, several are being evaluated for agronomic traits and yield parameters while four lines, GL 29029, GL29206, GL29212, GL29081 possessing high degree of resistance were crossed with susceptible high yielding cultivars BG 256 to improve resistance and to undertake molecular studies. Genotyping of F2 populations with SSR markers from the chickpea genome was done to identify markers potentially linked with AB and BGM resistance genes. In preliminary studies, of 120 SSR markers used, six (Ta 2, Ta 110, Ta 139, CaSTMS 7, CaSTMS 24 and Tr 29) were identified with polymorphic bands between resistant derivative lines and the susceptible parent. The study shows that wild species of Cicer are the valuable gene pools of resistance to AB and BGM. The resistant derivative lines generated here can serve as good pre-breeding material and markers identified can assist in marker assisted selection for resistance breeding.